The Strategy of the Muara Enim Regency Government in Encouraging Business Sector Participation to Increase Regional Revenue of Muara Enim Regency - Rinaldo Rinaldo; Kgs M. Sobri; Abdul Najib; Raniasa Putra (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the strategies employed by the Muara Enim Regency Government to enhance business sector participation in increasing Locally-Generated Revenue (PAD). Using a qualitative descriptive approach, the research explores the policies, initiatives, and outcomes associated with fostering collaboration between the government and private sector. Key strategies include the provision of fiscal incentives, streamlined licensing through digital platforms, investment promotion, and the alignment of Corporate Social Responsibility (CSR) programs with regional development goals. These initiatives have significantly improved the region's economic potential and contributed to a 20.64% increase in PAD from 2023 to 2024, reflecting the effectiveness of business engagement in local financial growth. Despite these achievements, challenges such as bureaucratic inefficiencies, inadequate infrastructure, and economic volatility persist. Supporting factors include strong government leadership, regulatory simplifications, and active collaboration with businesses, while obstacles like limited human resource capacity and dependency on extractive industries hinder long-term progress. The research highlights the necessity for continuous evaluation, diversification of revenue sources, and the integration of CSR with sustainable development plans to ensure regional economic resilience. This study provides valuable insights into the critical role of business sector participation in enhancing regional revenue and offers recommendations for replicating such strategies in other regions seeking economic self-sufficiency.